2007
DOI: 10.1523/jneurosci.0206-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cochlear Degeneration in Mice Lacking the F-Box Protein, Fbx2, a Glycoprotein-Specific Ubiquitin Ligase Subunit

Abstract: Little is known about the role of protein quality control in the inner ear. We now report selective cochlear degeneration in mice deficient in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 41 publications
6
62
0
Order By: Relevance
“…41 We and other have reported a similar phenomena with a stable FBG1-Skp1 dimer identified in the mouse cochlea, [30][31][32][33]48 where sequestration by FBG1 likely reduces the level of free Skp1. 33 In the FBG1 knockout mouse, total Skp1 levels are reduced in this tissue, likely to maintain constant levels of free Skp1. By analogy, FBG1 may sequester either Cul7 or APC2 into an inactive complex, allowing the adaptor protein to be present to rapidly bind other available E3 ligase subunits when required.…”
Section: Scf Ubiquitin Ligase Complex (Pdb Code 1ldk) Is Shown For Resupporting
confidence: 65%
See 2 more Smart Citations
“…41 We and other have reported a similar phenomena with a stable FBG1-Skp1 dimer identified in the mouse cochlea, [30][31][32][33]48 where sequestration by FBG1 likely reduces the level of free Skp1. 33 In the FBG1 knockout mouse, total Skp1 levels are reduced in this tissue, likely to maintain constant levels of free Skp1. By analogy, FBG1 may sequester either Cul7 or APC2 into an inactive complex, allowing the adaptor protein to be present to rapidly bind other available E3 ligase subunits when required.…”
Section: Scf Ubiquitin Ligase Complex (Pdb Code 1ldk) Is Shown For Resupporting
confidence: 65%
“…28 We and others also previously showed that FBG1 had a relatively low affinity for the SCF scaffold protein Cul1; in fact, rather than forming the canonical SCF complex, FBG1 primarily formed a dimer with Skp1. 22,23,[29][30][31][32] Finally we found that FBG1-mediated growth arrest required an intact F box, suggesting that the growth arrest may be mediated through the FBG1-Skp1 interaction.…”
Section: Fbg1 Interacts With Different Cullinmentioning
confidence: 57%
See 1 more Smart Citation
“…The SCF E3 ubiquitin ligase complex is widespread in organisms including plants and participates in the process of targeted protein degradation via the 26S proteasome, thereby controlling the compatibility of sexual hybridization between flowering plants (Skowyra et al 1997;Bodine et al 2001;Zheng et al 2002;Cardozo and Pagano 2004;Moon et al 2004;Nelson et al 2007;Xu et al 2013). We therefore investigated the expression patterns and levels of flower associated key genes encoding the subunits of the SCF complex in LA2405 (SI) and P86 (SC) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Co-transfections were performed as above with equimolar concentrations of DNA, and the total DNA did not exceed 6 g of DNA/10-cm plate. For SCF complex isolation, equimolar amounts of FBXO and Skp1, Cul1, and Rbx1 were transfected as described previously (30). Cells were harvested 48 h after transfection.…”
Section: Cloning and Plasmid Constructsmentioning
confidence: 99%